Simbolisme Ritual dan Legitimasi Kepemimpinan Adat: Kajian Etnografi Tradisi Munirin Reje Masyarakat Gayo Aceh Timur, Indonesia: Ritual Symbolism and Traditional Leadership Legitimacy: An Ethnographic Study on the Munirin Reje Tradition of the Gayo Community in East Aceh, Indonesia - Ahmad Nubli Gadeng; Asiah; Daska Azis; Ruliani Ruliani; Ramli Ramli (Al-Adabiya: Jurnal Kebudayaan dan Keagamaan, 2026)
This study explores Munirin Reje, a sacred purification and inauguration ritual practiced by the minority Gayo ethnic community in Simpang Jernih, East Aceh, Indonesia. The tradition plays a pivotal role in legitimizing customary leadership (Reje) and reinforcing social cohesion within the framework of local ethno-governance. Employing a qualitative micro-ethnographic approach, data were collected through participant observation, in-depth interviews, including with customary elders, and artifact analysis. The findings indicate that the ritual serves as a multidimensional instrument of political legitimacy and moral accountability. The symbolic use of water and peusijuek acts as a spiritual cleansing that elevates the Reje's moral authority. Importantly, the study highlights a crucial gendered mechanism of check-and-balance: the Bines dance performed by women serves as a platform for bottom-up social control, conveying constructive political criticism and advice through oral poetry prior to the leader's inauguration. Furthermore, genealogical knowledge transmission (Muyang–Datu–Awan–Ama) ensures the historical continuity of indigenous governance. The paper concludes that Munirin Reje is not merely a static ceremony, but a dynamic system of indigenous political ethics. To ensure its sustainability, the study recommends embedding its cultural values into inter-generational active participation and supporting its practice through local village development funds